Using dynamic BIM to improve construction safety culture - Amiri, Mojtaba; Saghatforoush, Ehsan; Laryea, Samuel (University of the Witwatersrand, Johannesburg, 2024)
Among the various studies that have addressed the application of BIM dynamics in domain of health and safety management, the lack of research regarding the impact of BIM dynamics on safety culture is clearly visible. These days, it is apparent that more and more construction technologies are currently being used for safety and health management. These technologies can be used in different construction applications to mitigate workplace hazards. Among these technologies, BIM and IoT has been shown to have significant potential in high-risk Environment, Health, and Safety (EHS) industries. Several researchers have started to explore the potential synergy between BIM and IOT. Dynamic BIM presents an influential pattern for applications to improve construction safety management. The main purpose of this paper is to demonstrate the necessity of research on the use of dynamic BIM in improving construction safety culture. Hence, the literature review method was used to identify the domains in which dynamic BIM has been applied. Prominent application domains in which dynamic BIM has been applied are construction operation and monitoring, facility management (FM), construction logistic and management, health and safety (H&S) management. Results show that no research has addressed the impact of dynamic BIM on safety culture. Therefore, research related to dynamic BIM and its impact on construction safety culture is necessary.
This paper presented at the Proceedings of the WABER SuDBE 2024 Conference, 30th – 31st July 2024, University of the Witwatersrand, Johannesburg, South Africa.
Keywords: Construction safety culture; Dynamic BIM; Health and safety management; Technologies; SDG-3: Good health and well-being